Faktor-Faktor yang Mempengaruhi Petugas Vaksinasi Covid-19 dalam Aktivitas Distribusi Vaksin Bagi Masyarakat dengan Metode Jemput Bola - Wirata, Resta Betaliani; Ikaningtyas, Nurlia; Adiyasa, Ratna Puspita; Timur, Sari Mutia; Kingkin, Dhinar Riski Linggar (Kisi Berkelanjutan: Sains Medis dan Kesehatan, 2025)
Introduction and Methods The door-to-door COVID-19 vaccination strategy requires adequate distribution facilities, such as vehicles and specialized storage to ensure vaccine quality. Additionally, vaccination officers play a crucial role in distributing vaccines to the community. Yakkum Emergency Unit (YEU) has consistently carried out vaccination efforts targeting high-risk groups in several regions using the door-to-door system to accelerate the process and reach more individuals in need. This method allows vaccinations to be administered directly at participants' homes. This study aims to analyze the factors influencing COVID-19 vaccination officers in distributing vaccines to the community through the door-to-door method. It is a cross-sectional study with a retrospective approach, collecting data online from vaccination officers. A total of 28 vaccinators were involved as research samples, selected using a total sampling technique. Results The study identified four factors examined in the distribution of COVID-19 vaccines using the door-to-door method. Three factors significantly influenced the vaccination activity: knowledge, willingness, and preparation. However, one factor, vaccine quality, showed no significant influence. Conclusion and Recommendations The study concludes that the willingness of healthcare workers is crucial for the success of COVID-19 vaccination efforts. Achievement of Sustainable Development Goals (SDGs) This study aims to identify the factors influencing vaccination officers in the distribution of vaccines using the mobile vaccination (jemput bola) method. This article contributes to Sustainable Development Goal (SDG) 3: Ensuring Healthy Lives and Promoting Well-being for All at All Ages. Specifically, it aligns with Target 3.b, which focuses on supporting research and development of vaccines and medicines for both communicable and non-communicable diseases, particularly those affecting developing countries, and ensuring affordable access to essential medicines and vaccines.